PSSI Crisis Response Strategy : Analysis of Kanjuruhan Tragedy News on Media Detik.com - PuspitaSari, Tarisa Hayu; Purworini, Dian (Institut Agama Islam Negeri Kendari, 2024)
A crisis is a situation or incident that can threaten an organization's reputation. One of the incidents that caused an organizational crisis was the Kanjuruhan tragedy. The existence of the Kanjuruhan tragedy, PSSI as a federation, is in the public spotlight for its response and actions. PSSI needs to give the right response so that the crisis does not have a negative impact on the organization's image. This research aims to find out the image restoration strategy used by PSSI in dealing with the crisis. This research uses Benoit's Image Restoration Theory. In describing PSSI's strategy, this research uses a descriptive quantitative method. The population used all news about PSSI's response to the Kanjuruhan tragedy published on Detik.com in October-November 2022. Sampling used the purposive sampling method. The results of this study show that PSSI uses all categories of image restoration strategies, such as denial, evasion of responsibility, reducing offensiveness, corrective action, and mortification. The evasion of responsibility strategy is the most dominant strategy, but it is not effective in improving the image because it avoids responsibility. Keywords: Content Analysis; Crisis; Image Restoration Theory; Reputation.